Tin sulphide prepared by sulphurisation process using metallic tin film precursor obtained from dc magnetron sputtering method - Ngamnit Wongcharoen; Thitinai Gaewdang (My University, 2017)
Thin films of tin sulphide were prepared by sulphurisation process of metallic Sn precursor at temperature of 300-500°C in excess ambient of sulphur using a graphite box in N2 atmosphere. Sulphurisation temperature at 300°C, the films were formed in SnS phase with orthorhombic structure. In contrast, the films were formed in SnS2 phase with hexagonal structure when sulphurisation temperature higher than 300°C. From absorption spectra, direct band gap increased from 1.70 to 2.45 eV with increasing sulphurisation temperature. From the transient photoconductivity measurements, persistent photoconductivity behavior was observed in the films sulphurised at 300 and 350°C. The decay current data are better fitted with multiple exponential function resulting in the several slow decay times. Density of trap states corresponding to its decay time was also evaluated from the decay current data.
Keywords: Orthorhombic crystal system; Photoconductivity; Chalcogenide Semiconductor Thin Films